2000
DOI: 10.1093/ps/79.9.1282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of normal yellow dent corn and high available phosphorus corn in combination with reduced dietary phosphorus and phytase supplementation for broilers grown to market weights in litter pens

Abstract: A study was conducted to determine the extent fecal P levels could be reduced while maintaining performance. Various strategies were employed including the use of a high available phosphorus hybrid of corn (HAPC), supplementation with phytase enzyme, and reduced dietary P levels. The use of HAPC resulted in a 50% reduction in phytate-bound dietary P as compared with a normal yellow dent corn (YDC) diet. Dietary nonphytate P was maintained at either NRC (1994) recommendations for appropriate age periods or redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…This result corroborates the findings of and Yan et al (2000), who reported the reduction of excreta P output by approximately 25% to 28%, respectively, when broiler diets were supplemented with phytase. Reported values for P level in broiler excreta vary widely, and can average even 2.1%, with a range of 1.3% to 3.4% .…”
Section: Resultssupporting
confidence: 92%
“…This result corroborates the findings of and Yan et al (2000), who reported the reduction of excreta P output by approximately 25% to 28%, respectively, when broiler diets were supplemented with phytase. Reported values for P level in broiler excreta vary widely, and can average even 2.1%, with a range of 1.3% to 3.4% .…”
Section: Resultssupporting
confidence: 92%
“…Earlier work with low-phytate corn was also successful in improving phosphorus utilization for pigs (Veum et al 2001) and broilers (Li et al 2000;Yan et al 2000;Waldroup et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that HAP maize contained more available P for layers than conventional maize and that only a small quantity of supplemental inorganic P was needed in order to maintain optimal laying performance (Snow et al, 2003). Corresponding results were obtained in studies with broilers, where it was demonstrated that the P in HAP maize was more available than in conventional maize and that diets based on HAP maize, with low levels of supplemental inorganic phosphates, allowed optimal production indices to be supported, while significantly decreasing the concentration of P in excreta (Li et al, 2000;Waldroup et al, 2000;Yan et al, 2000).…”
Section: Introductionmentioning
confidence: 71%